Challenges and Remedies in the Age of Antimicrobial Resistance Landscape: Ventilator-Associated Pneumonia - Azad Badhon, Md Farhan; Ahmed Chowdhury, Nadia Natasha; Azad, Farjan; Mondol, Abhijit; Kashyapi, Gaitri; Azad, Abul Kalam (Medicine Today, 2025)
Introduction: Ventilator-associated pneumonia (VAP) is a potentially fatal illness that arises in people who are on mechanical ventilation, generally in an intensive care unit (ICU) or a similar hospital setting. When bacteria or other pathogens infiltrate the lungs of a ventilated patient, VAP develops. This illness has the potential to cause serious complications, such as respiratory distress and lengthy hospitalization. Objective: This study aims to find and fix ICU ventilator-associated pneumonia management problems and possible solutions. Materials and Methods: This study was conducted in a medical college hospital for one year (January 2022-January 2023). 100 patients were included in this study based on the inclusion criteria. Result: 32 patients aged 60-69 years, mostly male (57), had common comorbidities: DM (70), hypertension (66), and heart failure (38). Major risk factors for VAP were age over 60 years, tracheostomy, Ng tube reintubation, enteral nutrition, witnessed aspiration, COPD, and coma. Patients diagnosed with cough were tested for C/S, blood was tested for C/S, and pleural fluid was tested for C/S. The major pathogens found were Pseudomonas, S. Aureus (including MRSA), Enterobacteriaceae, and Streptococcus.The antibiotics used in our study were carbapenem and linezolid. We used piperacillin-tazobactam and tigecycline. Conclusion: VAP may result in higher rates of morbidity, mortality, and medical expenses. Improving patient outcomes requires an early diagnosis and suitable therapy. Medicine Today 2025, Vol.37 (1): 52-56